Sulfur composition of MacEwan meteorites - Coyle, Amanda (My University, 2018)
Meteorites contain a wide variety of sulfur species: sulfates, sulfides, organic sulfur, and elemental sulfur. Sulfur in meteorites is thought to be in a form that resembles the sulfur on Earth before the formation of the hydrosphere. Thus, through investigations of the composition of these meteorites, insight can be gained regarding the formation of the Earth, and consequently, the formation of life. The goal of this project was to perfect wet chemistry techniques to deferentially extract the sulfur species to determine the relative masses of the different species. Multiple extractions with different solvents were used to separate the species based on their chemical and physical properties. Although all the species contain sulfur, the properties of them vary immensely. The MacEwan meteorites collection contains a wide variety of meteorites, including carbonaceous chondrites and a lunar sample. The techniques developed during the beginning phase of the project were applied to extract from one of the rocks, and will be used in future projects to extract sulfur from all rocks in the collection.
Presented on April 23, 2018 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: meteorites; sulfur